PENGARUH THRUST DEDUCTION FACTOR DAN WAKE FRACTION TERHADAP EFISIENSI PROPULSI AKIBAT PERUBAHAN DRAFT KAPAL - Muhammad Sawal Baital; Kusnindar Priohutomo; Jatmika Prajayastanda; Solichin Djazuli Sa'id (WAVE: Jurnal Ilmiah Teknologi Maritim, 2021)
This study is to investigate propulsion efficiency due to changes in draught of ship using data series and theoretical approach. A hard chain rescue boat with triplet screw was used for the study and to examine the effect of thrust deduction factor and wake fraction due to changes in draught of ship and its relevance to propulsion efficiency by observing hull and propeller interaction based on openwater test by Wageningen Data Series with cavitations analysis has been neglected. The study is done using hydrodynamics analysis for planning hull and using intersection between thrust characteristic curve with openwater test data series for fixed pitch propeller. The result indicated that the changes in ship draught are very influential on the changes in thrust deduction factor and wake fraction value which is one of the contributing factor to change the propulsion efficiency value 1% - 5%.